อิทธิพลของแสงจากหลอดไดโอดเปล่งแสง (LED) ต่อการเจริญเติบโตของผักสลัด 4 ชนิด - อ่อนศรี กษิดิ์เดช; จันจุฬา ณัฐพงค์; ลดาวัลย์ จิรภัทร (Thai Journal of Science and Technology, 2020)
Lettuce is a favorite for growing by hydroponic or soilless culture systems as the trend of the growing up business. This experiment works on 4 types of lettuce, i.e. red oak, cos, green coral and green oak. These are grown by hydroponics system with 3 different LED light color ratios, i.e. only white light (WL), 2 white: 1 blue: 2 red (2W1B2R), and 2 white: 2 blue: 1 red (2W2B1R) in 10 replications each. The experiment was designed in a completely randomized design (CRD). The result showed that the system with 2W1B2R supported the great growth rate of the 4 types of lettuce. They have the most leave length and shrub canopy. Moreover, the system with the WL enhanced the most of leave width, fresh/dried weight of stem and root as well as amount of chlorophyll A, chlorophyll B, total chlorophyll and total carotenoid in the 4 types of lettuce. As the results, this information can be an approach to the commercial production of the lettuce.